Life Satisfaction and Character Strengths in Ecuatorian Adolescents - Yépez-Tito, Pula A.; Ferragut-Ortiz-Tallo, Marta; Cóndor-Guerrón, Shally; Blanca-Mena, María José (Springer, 2021)
There is empirical evidence that life satisfaction (LS) in adolescence is associated with adequate development and future well-being. Research into the factors underpinning LS can therefore help to promote healthier development of societies. The aim of this study was to extend knowledge about LS among adolescents in Ecuador, a Latin American country for which research on this topic is lacking. Specifically, we analyze the relationship between LS and character strengths, controlling for gender, age, socioeconomic status, and family structure. Participants were 659 adolescents (43.1% female) aged between 12 and 18 years who completed the Students’ Life Satisfaction Scale (SLSS) and the Values in Action Inventory of Strengths for Youth (VIA-Y). Their parents or legal guardians completed the Survey of Socioeconomic Stratification (SSES). Correlation analysis and regression modeling were performed. Results showed that LS was not related to age or socioeconomic status, but there was a significant association with gender and family structure, insofar as boys and adolescents living in intact families reported higher levels of LS. Overall, the majority of character strengths were positively related to LS. After eliminating overlap between strengths and controlling for sociodemographic variables, the strengths of hope, zest, love, and prudence significantly predicted LS. We discuss how these strengths, related to the cognitive component of well-being, may play a protective role against difficulties during adolescence. Character strengths-based interventions are proposed to promote healthy development in Ecuadorian adolescents.
Keywords: Bienestar social; Well-being; Virtues; Youth; Latin America